Macrocyclic Gd3+ Complexes with Pendant Crown Ethers Designed for Binding Zwitterionic Neurotransmitters. Issue 31 (26th June 2015) - Oukhatar , Fatima; Meudal, Hervé; Landon, Céline; Logothetis , Nikos K.; Platas‐Iglesias, Carlos; Angelovski, Goran; Tóth, Éva
Abstract A series of Gd3+ complexes exhibiting a relaxometric response to zwitterionic amino acid neurotransmitters was synthesized. The design concept involves ditopic interactions 1) between a positively charged and coordinatively unsaturated Gd3+ chelate and the carboxylate group of the neurotransmitters and 2) between an azacrown ether appended to the chelate and the amino group of the neurotransmitters. The chelates differ in the nature and length of the linker connecting the cyclen‐type macrocycle that binds the Ln3+ ion and the crown ether. The complexes are monohydrated, but they exhibit high proton relaxivities (up to 7.7 mM−1 s−1 at 60 MHz, 310 K) due to slow molecular tumbling. The formation of ternary complexes with neurotransmitters was monitored by 1H relaxometric titrations of the Gd3+ complexes and by luminescence measurements on the Eu3+ and Tb3+ analogues at pH 7.4. The remarkable relaxivity decrease (≈80 %) observed on neurotransmitter binding is related to the decrease in the hydration number, as evidenced by luminescence lifetime measurements on the Eu3+ complexes. These complexes show affinity for amino acid neurotransmitters in the millimolar range, which can be suited to imaging concentrations of synaptically released neurotransmitters. They display good selectivity over non‐amino acid neurotransmitters (acetylcholine, serotonin, and noradrenaline) and hydrogenphosphate, but selectivity over hydrogencarbonate was not achieved.